2018
DOI: 10.1097/aog.0000000000002375
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Bupivacaine During Robotic Colpopexy and Posterior Repair

Abstract: ClinicalTrials.gov, NCT02449915.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…Liposomal bupivacaine (Exparel ® , Pacira Pharmaceuticals, San Diego, CA) was approved for local surgical site injection for postoperative pain after haemorrhoidectomy and bunionectomy by the US FDA in 2011 (Yeung et al 2018). Each liposomal bupivacaine particle (DepoFoam ® , Pacira Pharmaceuticals, Parsippany, NJ) is composed of a honeycomb-like structure of internal aqueous chambers containing encapsulated bupivacaine (Mazloomdoost et al 2017).…”
Section: Pain Management: Bupivacainementioning
confidence: 99%
See 1 more Smart Citation
“…Liposomal bupivacaine (Exparel ® , Pacira Pharmaceuticals, San Diego, CA) was approved for local surgical site injection for postoperative pain after haemorrhoidectomy and bunionectomy by the US FDA in 2011 (Yeung et al 2018). Each liposomal bupivacaine particle (DepoFoam ® , Pacira Pharmaceuticals, Parsippany, NJ) is composed of a honeycomb-like structure of internal aqueous chambers containing encapsulated bupivacaine (Mazloomdoost et al 2017).…”
Section: Pain Management: Bupivacainementioning
confidence: 99%
“…A slow-release mechanism involving reorganization of the barrier lipid membranes is sustained for up to 92 h with concomitant pain control for up to 72 h, as compared to 7-12 h with standard bupivacaine. Studies show bupivacaine decreased pain compared to placebo, the use of opioids and the hospital costs (Yeung et al 2018;Mazloomdoost et al 2017;Sabesan et al 2017;Declaire et al 2017;Smith et al 2017;Mcgraw-tatum et al 2017;Abildgaard et al 2017;Alijanipour et al 2016;Davidovitch et al 2017). Although the liposomal bupivacaine is not a nanoparticle (3-30 μm mean diameter), it is mentioned here because it is one of the most recent liposomal formulations approved.…”
Section: Pain Management: Bupivacainementioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35][36][37] . Six studies included patients undergoing abdominal hysterectomy, laparoscopy with perineal/vaginal procedures or obstetric surgery [27][28][29][30][31][32] ; 3 studies were trial registrations of full texts that were already included in the review [33][34][35] ; 2 studies used different interventions e.g. sacrocolpopexy [36,37] ; and 1 study assessed a different outcome -gluteal pain instead of perineal pain.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of RSC concluded that RSC has more post-operative pain than LSC (22,23). Interestingly, when bupivacaine was injected into the incision sites during a RSC, there was no significant improvement in pain scores as compared to saline (72). When RSC was compared to vaginal native tissue repair, the RSC group used fewer narcotic equivalents although there were no differences in pain scales (73).…”
Section: Surgical Risks/complications Of Robotic-assisted Repairsmentioning
confidence: 99%